Embedding L2 Listening Homework in Metacognitive Intervention: Listening Comprehension Development - Bozorgian, Hossein; Muhammadpour, Meysam; Mahmoudi, Elahe (Frontiers in Education, 2022)
A review of the various approaches to L2 listening instruction suggests that they were more of text- or communication-oriented approaches and less of learner-oriented ones. More recently, the focus has shifted to engage L2 listeners in their own listening comprehension process through strategy instruction inside the classroom and strategy use outside the classroom. In this regard, Vandergrift and Goh (2012) suggested a metacognitive approach to L2 listening instruction in which listening homework is assigned to L2 listeners as an extensive listening activity. Thus, the present article reports on a qualitative study that explores the role of embedding listening homework in metacognitive intervention in the case of English as Foreign Language listening comprehension and the problems learners encounter during listening. A group of intermediate-level male and female learners (N = 25) speaking Persian as the first language participated in embedded listening tasks. As part of a metacognitive intervention, the learners were given listening homework for which they were requested to view five news programs drawn from the BBC website for five weeks and complete diaries with a self-directed listening guide before, during, and after watching the programs. Totally, 116 diary entries were analyzed and data about factors influencing their listening comprehension processes and the actual notes they took during planning, monitoring, and evaluating stages of listening comprehension were collected. To categorize and analyze the diary entries, Goh’s (1999) framework was used as the analytical framework. Results indicated that diaries with a self-directed listening guide served pedagogical purposes by raising the learners' metacognitive knowledge and providing them with opportunities to plan, monitor, and evaluate their unseen listening processes. It helped listeners to reflect on their listening homework, find the gap, take action to resolve their listening problems, and experience a sense of achievement and confidence. Possible reasons for findings are outlined and recommendations for future research are presented.